Human Resource Management In Optimizing The Performance Of Teaching Staff In Integrated Islamic Elementary Schools - Rahman, Habibur; Romlah; Septuri (Journal of Advanced Islamic Educational Management, 2025)
This research is motivated by the importance of human resource management (HRM) in optimizing the performance of educators, especially in schools based on Islamic values. SDIT Al Kholis South Lampung was chosen as the object because of its uniqueness in implementing a human resource management approach that is integrated with the development of ruhiyah and Islamic values. The purpose of this study is to analyze the implementation of human resource management functions which include planning, recruitment, performance appraisal, training and development, and fostering work relations. The research used a phenomenological approach with data collection techniques through observation, in-depth interviews, and documentation. The data were analyzed qualitatively through the stages of reduction, presentation, and conclusion drawing, and tested for validity through triangulation of sources and techniques. The results showed that human resource management at Al Kholis Integrated Islamic Elementary School in South Lampung is carried out systematically and effectively. The main findings include the existence of a weekly ruhiyah coaching program and the integration of Islamic values in the curriculum as a performance improvement strategy. These two aspects are an important novelty in the study of Islamic education management.